Do Rockwood frailty score and Charlson comorbidity index help to risk stratify outpatient versus inpatient management of acute decompensated heart failure?. (25th November 2020) - Neoh, K.A.I; Sevdynidis, L; Hatherley, J; Tay, J; Douglas, H; Akpan, A; Sankaranarayanan, R
Abstract: Introduction: Acute decompensated heart failure (ADHF) is associated with frailty and co-morbidities which influence prognosis. The Rockwood Frailty Score (RFS) and age-adjusted Charlson co-morbidity index (CCI) have been used to predict outcomes in hospitalised ADHF patients. Purpose: To describe the relationship of CCI, RFS and clinical risk score -Get With The Guidelines Score (GWTG) with mortality in ADHF treated as outpatients (OP) versus hospitalised inpatients (IP). Methods: This retrospective analysis compared 2 cohorts of consecutive ADHF patients - hospitalised in-patients (IP) versus outpatients (OP) who were treated with bolus intravenous diuretics in a specialist heart failure nurse delivered OP HF unit (Ambulatory HF Unit -AHFU) with input from various specialties (renal, palliative, ascitic, pleural teams) from Nov 16 to Dec 17. Mean follow-up duration was similar for both groups (IP=19.5±4.1 months; OP=19.3±3.9 months, p=0.6). Mortality was compared at 1, 3 and 12 months based on RFS (no frailty <5, mild to moderate frailty 5/6, severe frailty - 7 to 9). Results were expressed as mean±SD and analysed using One-Way ANOVA and Chi-squared with Fisher's exact test test. Results: 410 consecutive patients (482 admissions) were hospitalised (inpatients -IP) and 231 OP (289 OP visits) were treated in the AHFU. IP group had significantly higher mean CCI (IP=6.55±2; OP=6.10±1.9; p=0.006) and mean RFS (IP 5.2±1.2; OP 4.9±1.1; p=0.002). Mean Clinical Risk Score GWTG was similar (IP=38.9±7.2; OP=38.4±6.6; p=0.44). Mean survival was significantly lower in IP (IP=378±270 days; OP=437±228; P=0.003). As shown in the table higher RFS predicts increased mortality risk (1 month, 3 month and 12 month). Conclusions: Rockwood Frailty Score predicts mortality in ADHF and assessment of RFS can play an important role in risk stratifying and decision-making in addition to clinical risk-scores, with regards to suitability for outpatient treatment of ADHF. Funding Acknowledgement: Type of funding source: None